Dietary Inflammatory Index and Health Outcomes: An Umbrella Review of Systematic Review and Meta-Analyses of Observational Studies - Liu, Fang-Hua; Liu, Chuan; Gong, Ting-Ting; Gao, Song; Sun, Hui; Jiang, Yu-Ting; Zhang, Jia-Yu; Zhang, Meng; Gao, Chang; Li, Xin-Yu; Zhao, Yu-Hong; Wu, Qi-Jun (Frontiers in Nutrition, 2021)
Background and Aims: The dietary inflammatory index (DII) is associated with non-communicable disease. We conducted an umbrella review to systematically evaluate meta-analyses of observational studies on DII and diverse health outcomes. Methods: We comprehensively searched the PubMed, Web of Science, and Embase databases to identify related systematic reviews and meta-analyses of observational studies. Those investigating the association between DII and a wide range of health outcomes in humans were eligible for inclusion. For each meta-analysis, we estimated the summary effect size by using fixed and random effects models, the 95% confidence interval, and the 95% prediction interval. We assessed heterogeneity, evidence of small-study effects, and excess significance bias. Results: The umbrella review identified 35 meta-analyses assessing associations between DII and various health outcomes: cancer (n = 24), mortality (n = 4), metabolic (n = 4), and other (n = 3). The methodological quality was high or moderate. Of the 35 meta-analyses, we observed highly suggestive evidence for harmful associations between digestive tract cancer, colorectal cancer, overall cancer, pharyngeal cancer, UADT cancer, and CVD mortality. Moreover, 11 harmful associations showed suggestive evidence: hormone-dependent cancer, rectal cancer, colon cancer, breast and prostate cancer, gynecological cancer, breast cancer, ovarian cancer, colorectal cancer, prostate cancer, all-cause mortality, and depression. Conclusion: DII is likely to be associated with harmful effects in multiple health outcomes. Robust randomized controlled trials are warranted to understand whether the observed results are causal. Systematic Review Registration: CRD42021218361